Rifampicin-Resistance Mutations in the rpoB Gene in Bacillus velezensis CC09 have Pleiotropic Effects - Cai, Xun-Chao; Xi, Huan; Liang, Li; Liu, Jia-Dong; Liu, Chang-Hong; Xue, Ya-Rong; Yu, Xiang-Yang (Frontiers in Microbiology, 2017)
Rifampicin resistance (Rifr) mutations in the RNA polymerase β subunit (rpoB) gene exhibit pleiotropic phenotypes as a result of their effects on the transcription machinery in prokaryotes. However, the differences in the effects of the mutations on the physiology and metabolism of the bacteria remain unknown. In this study, we isolated seven Rifr mutations in rpoB, including six single point mutations (H485Y, H485C, H485D, H485R, Q472R, and S490L) and one double point mutation (S490L/S617F) from vegetative cells of an endophytic strain, B. velezensis CC09. Compared to the wild-type (WT) strain (CC09), the H485R and H485D mutants exhibited a higher degree of inhibition of Aspergillus niger spore germination, while the H485Y, S490L, Q472R, and S490L/S617F mutants exhibited a lower degree of inhibition due to their lower production of the antibiotic iturin A. These mutants all exhibited defective phenotypes in terms of pellicle formation, sporulation, and swarming motility. A hierarchical clustering analysis of the observed phenotypes indicated that the four mutations involving amino acid substitutions at H485 in RpoB belonged to the same cluster. In contrast, the S490L and Q472R mutations, as well as the WT strain, were in another cluster, indicating a functional connection between the mutations in B. velezensis and phenotypic changes. Our data suggest that Rifr mutations can not only be used to study transcriptional regulation mechanisms, but can also serve as a tool to increase the production of bioactive metabolites in B. velezensis.